High-Pressure Investigation of the I–N System: Discovery of the Nitric Ozonide [N3]3– (“Ozonitride”) Species and Multicenter Bonding in Iodine Frameworks - James Spender; Linda Reitz; Umbertoluca Ranieri; Akun Liang; Sarah Bolton; Qian Zhang; Ryan Stewart McWilliams; Bernhard Massani; Stella Chariton; Vitali Prakapenka; Eleanor Lawrence Bright; Nico Giordano; et al. (Journal of the American Chemical Society, 2026)
Abstract Despite binary nitrides being heavily investigated at high pressures in the past decade, nitrogen halides are still a terra incognita at pressures exceeding 1 bar. Due to the unique chemistry of halogens, they are fertile grounds for the discovery of novel nitrogen species. Here, we report the high-pressure investigation of the I–N system up to 120 GPa using laser-heated diamond anvil cells and the synthesis of the first two thermodynamically stable binary iodine–nitrogen compounds, I4(N2)3 and I2(N2)(N3), formed from 81 and 95 GPa, respectively. Their crystal structures were solved and refined through synchrotron single-crystal X-ray diffraction measurements. I4(N2)3 is comprised of a layered polymeric iodine framework of hexagonal iodine units and infinite linear iodine chains─both evidenced to feature multicenter bonding─along with N2 dimers. In contrast, I2(N2)(N3) exhibits corrugated and distorted I6 layers along with N2 dimers as well as a hitherto unknown nitrogen species, [N3]3–. This anion is both isosteric and isoelectronic with ozone (O3), leading to its designation as a nitric ozonide (or “ozonitride” for simplicity). The stability domain of each compound is investigated, and their bulk modulus determined. Accompanying density functional theory calculations provide further insight into the crystal chemistry, stability regime, and physical properties of the two iodine–nitrogen compounds.